The adaptive capacity of smallholder mixed-farming systems to the impact of climate change : the case of KwaZulu-Natal in South Africa - Mthembu, Nonhlanzeko N.; Zwane, Elliot M. (Jàmbá - Journal of Disaster Risk Studies, 2017)
Climate change poses a serious threat to efforts by developing countries to ensure food security and poverty reduction. The National Development goals of South Africa envisage the agricultural sector as a key driver for job creation and economic growth. This article seeks to investigate the adaptive capacity of the Ncunjane farming community in Msinga, KwaZuluNatal in response to drought spells of 2010 and 2014. This article draws on data collected using both qualitative and quantitative methods in 2011 and later in 2015 with the data analysed through the Statistical Package for Social Science to determine significant correlations between variables. Analysis of the vulnerability and adaptive capacity is performed using conceptual framework. This study found that both smallholder farmers who engaged in livestock and crop production have experienced high cattle mortalities and stagnant crop productivity, which in turn put pressure on already constrained disposable household income because of increased food costs and agricultural input costs, particularly supplementary animal feed. Cattle owners were more vulnerable to drought because of poor risk management and thus became highly dependent on government to provide drought relief. Application for government drought relief was found not to be effective in cases of large herds of cattle. Variability of rainfall and prolonged heat spells has a significant impact on the sustainability of smallholder mixed-farming systems, leaving agriculture as a highly questionable form of livelihood for rural farming communities such as Msinga. The article recommends strengthened institutional mechanisms so that stakeholders should play a more meaningful role within provincial and local agriculture in leveraging government support but places emphasis on the adoption of innovative strategies that can potentially yield significantly resilient smallholder mixed-farming systems in the wake of climate variability.
Journal article published in the Jàmbá - Journal of Disaster Risk Studies
Keywords: Smallholder mixed-farming; Climate change; Food security; Developing countries; Climatic changes